Tracking Targeted Bimodal Nanovaccines: Immune Responses and Routing in Cells, Tissue, and Whole Organism - Cruz, Luis J. (2014)
Dendritic cells (DCs) are the most potent antigen-presenting cells (APCs), involved in the induction of immunity and currently exploited for antitumor immunotherapies. An optimized noninvasive imaging modality capable of determining and quantifying DC-targeted nanoparticle (NP) trajectories could provide valuable information regarding therapeutic vaccine outcome. Here, targeted poly(d,l-lactide-co-glycolide) nanoparticles (PLGA NPs) recognizing DC receptors were equipped with superparamagnetic iron oxide particles (SPIO) or gold nanoparticles with fluorescently labeled antigen. The fluorescent label allowed for rapid analysis and quantification of DC-specific uptake of targeted PLGA NPs in comparison to uptake by other cells. Transmission electron microscopy (TEM) showed that a fraction of the encapsulated antigen reached the lysosomal compartment of DCs, where SPIO and gold were already partially released. However, part of the PLGA NPs localized within the cytoplasm, as confirmed by confocal microscopy. DCs targeted with NPs carrying SPIO or fluorescent antigen were detected within lymph nodes as early as 1 h after injection by magnetic resonance imaging (MRI). Despite the fact that targeting did not markedly affect PLGA NP biodistribution on organism and tissue level, it increased delivery of NPs to DCs residing in peripheral lymph nodes and resulted in enhanced T cell proliferation. In conclusion, two imaging agents within a single carrier allows tracking of targeted PLGA NPs at the subcellular, cellular, and organismal levels, thereby facilitating the rational design of in vivo targeted vaccination strategies.